Evidence-Based Approach to Nerve Gap Repair in the Upper Extremity: A Review of the Literature and Current Algorithm for Surgical Management. (June 2020) - Huayllani, Maria T.; Boczar, Daniel; Forte, Antonio J.; Rinker, Brian
Abstract : Abstract: The upper extremity is the most common site for nerve injuries. In most cases, direct repair can be performed, but when a critical gap occurs, special techniques must be used to enhance nerve regeneration and allow recovery of sensory and motor functions. These techniques include the use of autografts, processed nerve allografts, and conduits. However, surprisingly few studies have compared outcomes from the different methods of nerve gap repair in a rigorous fashion. There is a lack of evidence-based guidelines for the management of digital and motor and mixed nerve injuries with a nerve gap. The purpose of this study is to perform a comprehensive literature review and propose a rational algorithm for management of nerve injuries with a critical gap.